Structure–Function Relationship of Aminopeptidase P from Pseudomonas aeruginosa - Peng, Cui-Ting; Liu, Li; Li, Chang-Cheng; He, Li-Hui; Li, Tao; Shen, Ya-Lin; Gao, Chao; Wang, Ning-Yu; Xia, Yong; Zhu, Yi-Bo; Song, Ying-Jie; Lei, Qian; et al. (Frontiers in Microbiology, 2017)
PepP is a virulence-associated gene in Pseudomonas aeruginosa, making it an attractive target for anti-P. aeruginosa drug development. The encoded protein, aminopeptidases P (Pa-PepP), is a type of X-prolyl peptidase that possesses diverse biological functions. The crystal structure verified its canonical pita-bread fold and functional tetrameric assembly, and the functional studies measured the influences of different metal ions on the activity. A trimetal manganese (Mn) cluster was observed at the active site, elucidating the mechanism of inhibition by metal ions. Additionally, a loop extending from the active site appeared to be important for specific large-substrate binding. Based on the structural comparison and bacterial invasion assays, we showed that this non-conserved surface loop was critical for P. aeruginosa virulence. Taken together, these findings can extend our understanding of the catalytic mechanism and virulence-related functions of Pa-PepP and provide a solid foundation for the design of specific inhibitors against pathogenic-bacterial infections.